Relationships of convolution products, generalized transforms, and the first variation on function space - Seung Jun Chang; Jae Gil Choi (International Journal of Mathematics and Mathematical Sciences)
We use a generalized Brownian motion process to define the generalized Fourier-Feynman transform, the convolution product, and the first variation. We then examine the various relationships that exist among the first variation, the generalized Fourier-Feynman transform, and the convolution product for functionals on function space that belong to a Banach algebra S(Lab[0,T]). These results subsume similar known results obtained by Park, Skoug, and Storvick (1998) for the standard Wiener process.